Lactobacillus paragasseri OLL2809 Improves Depression-Like Behavior and Increases Beneficial Gut Microbes in Mice - Hashikawa-Hobara, Narumi; Otsuka, Ami; Okujima, Chihiro; Hashikawa, Naoya (Frontiers in Neuroscience, 2022)
Lactobacillus paragasseri OLL2809 is a probiotic bacterial strain isolated from healthy human feces. While OLL2809 has been studied for its immunomodulatory activities, its effect on depressive-like behaviors remains unclear. In this study, we used a mouse model of social defeat stress to investigate whether oral administration of OLL2809 ameliorates depressive-like behavior. C57BL6 male mice were administered OLL2809 for 2 weeks following a 4-week period of social defeat stress. Although OLL2809 did not affect serum corticosterone levels, it ameliorated depression-like behaviors, and it induced neurite outgrowth in the hippocampal dentate gyrus. The 16S rRNA amplicon sequence analyses revealed that family-level gut microbiota composition was affected by stress and OLL2809 administration. Additionally, Akkermansia muciniphila, Bifidobacterium and Lactobacillus were significantly increased by OLL2809 treatment. LEfSe analysis suggested that the antidepressive effect of OLL2809 may be mediated by increases in other microorganisms, such as Erysipelotrichaceae uncultured. Our findings suggest that L. paragasseri OLL2809 may have potential in microbiome therapeutics.